Unlocking the Secrets of Profitability: Investigating the Role of Research and Development - Mubarok, Faizul; Sultan, Zulkifli; Wibowo, Martino; Wongsuwatt, Sippavitch (Jurnal Manajemen Teori dan Terapan| Journal of Theoretical and Applied Management, 2023)
Objective: The manufacturing sector is crucial for the development of emerging economies. This study aims to examine how research and development influence the firm’s financial performance of manufacturing firms. Design/Methods/Approach: This study employs publicly listed Indonesian firms’ panel data from 2017 to 2021. The data are analyzed using the panel data approach. Findings: The results indicate that research and development positively affect firm financial performance. Originality: Research and development investment has been commonly carried out in developed countries but is still very limited in developing countries. This study focuses on the role of investment in research and development in determining the financial performance of companies in an emerging country. Practical/Policy implication: Companies should prioritize cash and risk management to enable business expansion and innovation. Government support can be provided through tax incentives, R&D assistance, financing access, and public recognition of companies with high profitability. These incentives are aimed at enhancing economic growth and corporate competitiveness.